A dispersant for lithium ion battery graphite negative electrode and a preparation method and application thereof
Patent Information
- Application Number
- CN202611111239.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
然而,该方案下浆料的固含量仅能达到约50%,进一步提升固含量时降粘效果明显受限,且增塑剂的添加量较高,达到0.5%以上,可能对电池性能产生不利影响
本发明通过将降粘稳粘组分与防开裂组分复配,利用两类组分在不同阶段发挥互补作用,取得了显著的协同技术效果。具体而言,降粘稳粘组分通过对石墨颗粒的定向吸附形成双电层和空间位阻层,有效克服了高固含量条件下石墨颗粒间的范德华引力,打破了颗粒团聚形成的空间网络结构,释放了被束缚的自由水,显著降低了浆料的粘度并提高了流动性;同时,由于降粘稳粘组分在石墨表面形成的吸附层具有良好的热力学稳定性,不易在静置过程中发生脱附,颗粒间的静电斥力和空间位阻能够在较长时间内维持有效,阻止了颗粒因重力作用和范德华力作用而发生的沉降和硬团聚,赋予浆料优异的静态稳定性。防开裂组分其分子中的醚键氧原子与水分子形成氢键延缓了局部水分的蒸发速率使干燥更加均匀,同时其柔性分子链在干燥后以薄膜形式存在于石墨颗粒之间和颗粒与集流体之间,能够通过构象变化吸收和分散干燥过程中的应力集中,增强膜层的整体柔韧性和附着力,有效防止了极片在干燥过程中出现的开裂。两类组分的上述功能互不干扰且功能互补,共同实现了降粘、稳粘、防沉降与防开裂的综合技术效果,最终制得了高固含量、低粘度的负极浆料。
Smart Images

Figure CN122992067A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a dispersant for graphite anodes of lithium-ion batteries, its preparation method, and its application. Background Technology
[0002] The negative electrode slurry for lithium-ion batteries typically consists of graphite active materials, conductive agents, binders, and solvents. As battery manufacturing demands increasingly higher production efficiency, product consistency, and energy density, increasing the solid content of the slurry has become a crucial direction for process improvement. Increasing the solid content reduces the drying load after coating, shortens drying time, and decreases solvent migration within the electrode, thereby suppressing binder segregation and electrode cracking. It also helps improve the compaction density of the electrode. However, when the solid content of the graphite negative electrode slurry exceeds 50%, the viscosity of the slurry increases sharply, and its fluidity deteriorates significantly, making it difficult to meet the requirements of high-speed coating processes. Furthermore, graphite particles in high-solid-content slurries are prone to sedimentation and agglomeration, leading to increased slurry fineness and decreased stability. The wet film after coating is also prone to cracking during the drying process, affecting electrode quality and battery performance.
[0003] To address the aforementioned issues, the industry typically adds dispersants or plasticizers to the slurry. For example, Chinese patent CN116190651A discloses a method for improving the fluidity of negative electrode slurry, using ethylene carbonate and / or propylene carbonate as plasticizers to reduce the viscosity of the negative electrode slurry. However, this method only achieves a solid content of approximately 50% in the slurry; further increasing the solid content significantly limits the viscosity-reducing effect, and the amount of plasticizer added is relatively high, exceeding 0.5%, which may adversely affect battery performance. Currently, there is a lack of a multifunctional dispersant solution that can simultaneously achieve effective viscosity reduction at high solid content, long-term stable storage of the slurry, and inhibition of cracking during electrode drying.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a dispersant for graphite anodes of lithium-ion batteries, its preparation method, and its application.
[0006] This invention is implemented as follows: In a first aspect, the present invention provides a dispersant for a graphite anode of a lithium-ion battery, the dispersant comprising a viscosity-reducing and viscosity-stabilizing component and a crack-preventing component; The viscosity-reducing and viscosity-stabilizing components include one or more of sodium gluconate, sodium tartrate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate. The anti-cracking component is one or more of polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, and polyvinylpyrrolidone.
[0007] In an optional embodiment, the viscosity-reducing and tack-stabilizing component has a mass percentage content of 10% to 20% in the dispersant; the crack-preventing component has a mass percentage content of 5% to 20% in the dispersant.
[0008] In an optional embodiment, the dispersant further includes a solvent; the solvent is a polar solvent. Furthermore, the solvent is one or more of water, ethanol, and acetone.
[0009] In an optional embodiment, the viscosity-reducing and tack-stabilizing component is sodium gluconate, sodium tartrate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or a combination of sodium gluconate and sodium tartrate.
[0010] In an optional embodiment, the anti-cracking component is polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, polyvinylpyrrolidone, or a combination of polyethylene glycol monomethyl ether and alkylphenol polyoxyethylene ether.
[0011] In an optional embodiment, the molecular weight of the polyethylene glycol monomethyl ether is 200 to 2000.
[0012] Secondly, the present invention provides a method for preparing a dispersant for a graphite anode in a lithium-ion battery as described in the foregoing embodiments, comprising the following steps: The viscosity-reducing and stabilizing components and the crack-preventing components are dispersed in a solvent to obtain the dispersant.
[0013] Thirdly, the present invention provides a negative electrode slurry comprising graphite, a conductive agent, a thickener, a binder, a solvent, and a dispersant as described in the foregoing embodiments.
[0014] In an optional embodiment, the solid content of the negative electrode slurry is 40% to 60%; the amount of dispersant added is 0.01% to 0.05% of the graphite mass.
[0015] Fourthly, the present invention provides a battery comprising the negative electrode slurry as described in the foregoing embodiments.
[0016] The present invention has the following beneficial effects: This invention achieves significant synergistic effects by combining a viscosity-reducing and stabilizing component with a crack-preventing component, utilizing the complementary effects of the two components at different stages. Specifically, the viscosity-reducing and stabilizing component forms an electric double layer and a steric hindrance layer through directional adsorption of graphite particles, effectively overcoming the van der Waals forces between graphite particles under high solids content conditions, breaking the spatial network structure formed by particle agglomeration, releasing bound free water, significantly reducing the viscosity of the slurry and improving its fluidity. At the same time, because the adsorption layer formed by the viscosity-reducing and stabilizing component on the graphite surface has good thermodynamic stability, it is not easy to desorb during static standing. The electrostatic repulsion and steric hindrance between particles can remain effective for a long time, preventing the sedimentation and hard agglomeration of particles due to gravity and van der Waals forces, thus giving the slurry excellent static stability. The anti-cracking component, with its ether-bonded oxygen atoms forming hydrogen bonds with water molecules, slows down the local evaporation rate of moisture, resulting in more uniform drying. Simultaneously, its flexible molecular chains exist as a thin film between graphite particles and between particles and the current collector after drying. This film can absorb and disperse stress concentration during the drying process through conformational changes, enhancing the overall flexibility and adhesion of the film and effectively preventing cracking of the electrode sheet during drying. The functions of the two types of components are independent and complementary, jointly achieving a comprehensive technical effect of viscosity reduction, viscosity stabilization, anti-settling, and anti-cracking, ultimately producing a high-solids-content, low-viscosity negative electrode slurry. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 The images show a comparison of the surface cracks on the negative electrode sheets prepared in Examples 1-11 and Comparative Examples 1-3 after drying.
[0019] Figure 2 Line graphs showing the solid content of the negative electrode slurries prepared in Examples 1-11 and Comparative Examples 1-3, as well as bar graphs comparing the initial viscosity and the viscosity after standing for 72 hours. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0021] In a first aspect, the present invention provides a dispersant for a graphite anode of a lithium-ion battery, the dispersant comprising a viscosity-reducing and viscosity-stabilizing component and a crack-preventing component; The viscosity-reducing and viscosity-stabilizing components include one or more of sodium gluconate, sodium tartrate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate. The anti-cracking component is one or more of polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, and polyvinylpyrrolidone.
[0022] The dispersant provided by this invention is used to reduce viscosity, stabilize viscosity, prevent sedimentation and cracking of graphite anode materials.
[0023] In negative electrode slurries, graphite is a layered material composed of sp2 hybridized carbon atoms. Within each layer, carbon atoms are covalently bonded to form stable six-membered ring structures, while the layers are bound together by van der Waals forces. Graphite layers exhibit high electron delocalization, resulting in a hydrophobic surface. When the solid content of the graphite negative electrode slurry increases to over 50%, the average spacing between graphite particles decreases sharply. Particles aggregate through van der Waals attraction and hydrophobic interactions, forming a spatial network structure that permeates the entire slurry. This leads to a sharp increase in slurry viscosity and decreased flowability, making it unsuitable for high-speed coating processes.
[0024] This invention combines anionic dispersants with viscosity-reducing and stabilizing effects with anti-cracking components. By utilizing the complementary effects of these two types of components at different stages, a comprehensive effect of viscosity reduction, stabilization, anti-settling, and anti-cracking is achieved. Specifically, the viscosity-reducing and stabilizing components contain hydrophobic carbon chains (or aromatic rings) and hydrophilic anionic groups. After the dispersant is added to the slurry, its hydrophobic ends are directionally adsorbed onto the hydrophobic surface of the graphite particles through hydrophobic interactions and / or π-π stacking interactions, while the hydrophilic anionic groups extend into the aqueous phase. This directional adsorption forms a negatively charged adsorption layer on the surface of graphite particles. The like charges on the surfaces of adjacent particles generate strong electrostatic repulsion. At the same time, the dispersant molecular chains adsorbed on the particle surface extend into the aqueous phase, forming a steric hindrance layer. When two particles approach each other, the overlap of the adsorption layers leads to an increase in local osmotic pressure and a decrease in conformational entropy, generating additional repulsive forces. Under the dual action of electrostatic repulsion and steric hindrance, the van der Waals attraction between graphite particles is effectively overcome, particle aggregation is broken, the spatial network structure in the slurry is dissociated, and the free water bound by the particle network is released, thereby significantly reducing the viscosity of the slurry and improving its fluidity.
[0025] The anti-cracking component mainly functions during the drying stage after slurry coating. During the drying process of the electrode, moisture evaporates from the surface of the wet film, creating a capillary pressure gradient within the film. When the solid content is high, the particles are tightly packed, the capillary diameter is small, the capillary pressure is high, and the drying stress increases accordingly. If the flexibility of the slurry film layer is insufficient to resist the accumulation of drying stress, cracks will form and propagate into macroscopic cracks. The anti-cracking component in this invention is a nonionic surfactant or polymer containing polyoxyethylene segments. The ether bond oxygen atoms in its molecules can form hydrogen bonds with water molecules, thereby forming a hydration layer on the particle surface and capillary walls, slowing down the local evaporation rate of moisture, making the drying of the entire wet film more uniform, and reducing the internal stress gradient caused by uneven drying rates. Simultaneously, after drying, the polyoxyethylene segments exist in thin film form between graphite particles and between particles and the current collector. Their flexible molecular chains can deform under external force, absorbing and dispersing stress concentration, enhancing the overall flexibility and adhesion of the film layer, thus effectively preventing the electrode from cracking during the drying process.
[0026] In an optional embodiment, the viscosity-reducing and tack-stabilizing component has a mass percentage content of 10% to 20% in the dispersant; the crack-preventing component has a mass percentage content of 5% to 20% in the dispersant.
[0027] In this application, when the content of the viscosity-reducing and stabilizing component is less than 10%, the adsorption amount of dispersant molecules on the surface of graphite particles is insufficient, and a continuous and dense charged adsorption layer cannot be formed on the surface of all graphite particles. The adsorption coverage in local areas of the particle surface is incomplete, resulting in weak electrostatic repulsion and steric hindrance effects. Strong van der Waals forces still exist between some particles, and the viscosity-reducing effect is insufficient. When the content of the viscosity-reducing and stabilizing component exceeds 20%, excessive dispersant molecules may form free micelles or aggregates in the slurry, increasing the ionic strength and osmotic pressure in the slurry. In addition, excessive residual viscosity-reducing and stabilizing components may adversely affect the electrochemical performance of the battery.
[0028] When the anti-cracking component content is below 5%, its concentration in the slurry is too low. After drying, the flexible film formed between graphite particles is discontinuous and cannot effectively cover the entire contact area between particles. This results in insufficient stress release, and the electrode may still crack. When the anti-cracking component content exceeds 20%, excessive anti-cracking component molecules may compete with the viscosity-reducing and stabilizing components for adsorption sites on the graphite particle surface, interfering with the ability of the viscosity-reducing and stabilizing components to form a dense adsorption layer on the particle surface, leading to a decrease in viscosity reduction. Simultaneously, excessive anti-cracking component may increase the amount of residual organic matter in the slurry after drying, which is detrimental to the electrode's conductivity and electrochemical performance.
[0029] In an optional embodiment, the dispersant further includes a solvent; the solvent is a polar solvent.
[0030] Furthermore, the solvent is one or more of water, ethanol, and acetone.
[0031] In this application, the anionic groups (such as carboxylate, sulfate, and sulfonate groups) in the viscosity-reducing and stabilizing components need to be fully dissociated in a polar solvent to generate negative charges, thereby forming a negatively charged adsorption layer on the surface of graphite particles.
[0032] In an optional embodiment, the viscosity-reducing and tack-stabilizing component is sodium gluconate, sodium tartrate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or a combination of sodium gluconate and sodium tartrate.
[0033] In an optional embodiment, the anti-cracking component is polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, polyvinylpyrrolidone, or a combination of polyethylene glycol monomethyl ether and alkylphenol polyoxyethylene ether.
[0034] In an optional embodiment, the molecular weight of the polyethylene glycol monomethyl ether is 200 to 2000.
[0035] Secondly, the present invention provides a method for preparing a dispersant for a graphite anode in a lithium-ion battery as described in the foregoing embodiments, comprising the following steps: The viscosity-reducing and stabilizing components and the crack-preventing components are dispersed in a solvent to obtain the dispersant.
[0036] Thirdly, the present invention provides a negative electrode slurry comprising graphite, a conductive agent, a thickener, a binder, a solvent, and a dispersant as described in the foregoing embodiments.
[0037] In an optional embodiment, the solid content of the negative electrode slurry is 40% to 60%; the amount of dispersant added is 0.01% to 0.05% of the graphite mass.
[0038] Solid content is a core parameter affecting the rheological properties of negative electrode slurry and the quality of the electrode sheet. This invention adds a very small amount of dispersant to the graphite negative electrode slurry and uses the viscosity-reducing and stabilizing components to form a charged adsorption layer on the surface of graphite particles, generating electrostatic repulsion and steric hindrance. This effectively overcomes the van der Waals attraction enhanced by high solid content, breaks the spatial network structure between particles, and releases the bound free water.
[0039] As a result, the solid content of the slurry can be increased from the conventional level of less than 50% to 56% or even 60%, while the viscosity of the system can still be maintained at a level suitable for coating. The direct benefits of high solid content include: reducing the amount of water that needs to be evaporated after coating, shortening drying time and production energy consumption; reducing the migration driving force of the binder during the drying process, reducing binder segregation, and improving the uniformity and bonding strength of the internal structure of the electrode; and increasing the compaction density of the electrode, which is conducive to improving the energy density of the battery. At the same time, the anti-cracking component delays water evaporation and releases stress through the formation of a hydration layer during the drying stage, further ensuring that the high solid content electrode will not crack after drying.
[0040] Fourthly, the present invention provides a battery comprising the negative electrode slurry as described in the foregoing embodiments.
[0041] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0042] Example 1 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20g of sodium gluconate, 10g of polyethylene glycol monomethyl ether, and 70g of deionized water. Add sodium gluconate and polyethylene glycol monomethyl ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0043] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse them evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.06 kg of the above dispersant (accounting for 0.03% of the graphite mass) and 11.51 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0044] (3) Performance testing The initial viscosity of the slurry was measured to be 5340 mPa·s using a rotational viscometer, the fineness was measured to be 16 μm using a scraper fineness meter, and the solid content was measured to be 56.4% using the drying method. After the slurry was sealed and allowed to stand for 72 hours, the viscosity was measured to be 7433 mPa·s, and the solid content was 56.3%. The slurry was coated onto copper foil, dried, and the surface of the electrode was observed. Figure 1 As shown, there is no obvious cracking.
[0045] Example 2 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium tartrate, 10 g of polyethylene glycol monomethyl ether, and 70 g of deionized water. Add sodium tartrate and polyethylene glycol monomethyl ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0046] (2) Preparation of negative electrode slurry Same as Example 1.
[0047] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 5611 mPa·s, the fineness to be 16 μm, and the solid content to be 56.5%. After standing for 72 hours, the viscosity was 8214 mPa·s, and the solid content to be 56.3%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0048] Example 3 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium dodecyl sulfate, 10 g of polyethylene glycol monomethyl ether, and 70 g of deionized water. Add sodium dodecyl sulfate and polyethylene glycol monomethyl ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0049] (2) Preparation of negative electrode slurry Same as Example 1.
[0050] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 12769 mPa·s, the fineness to be 19 μm, and the solid content to be 56.6%. After standing for 72 hours, the viscosity was 20231 mPa·s, and the solid content to be 56.4%. Figure 1 As shown, the electrode is slightly cracked.
[0051] Example 4 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium dodecylbenzenesulfonate, 10 g of polyethylene glycol monomethyl ether, and 70 g of deionized water. Add sodium dodecylbenzenesulfonate and polyethylene glycol monomethyl ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0052] (2) Preparation of negative electrode slurry Same as Example 1.
[0053] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 10581 mPa·s, the fineness to be 19 μm, and the solid content to be 56.8%. After standing for 72 hours, the viscosity was 19442 mPa·s, and the solid content to be 56.5%. Figure 1 As shown, the electrode is slightly cracked.
[0054] Example 5 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium gluconate, 10 g of alkylphenol polyoxyethylene ether, and 70 g of deionized water. Add sodium gluconate and alkylphenol polyoxyethylene ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0055] (2) Preparation of negative electrode slurry Same as Example 1.
[0056] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 6454 mPa·s, the fineness to be 17 μm, and the solid content to be 56.0%. After standing for 72 hours, the viscosity was 9063 mPa·s, and the solid content to be 55.8%. Figure 1 As shown, the electrode sheet has no obvious cracks.
[0057] Example 6 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium gluconate, 10 g of polyvinylpyrrolidone, and 70 g of deionized water. Add sodium gluconate and polyvinylpyrrolidone to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0058] (2) Preparation of negative electrode slurry Same as Example 1.
[0059] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 6066 mPa·s, the fineness to be 16 μm, and the solid content to be 56.3%. After standing for 72 hours, the viscosity was 8773 mPa·s, and the solid content to be 56.0%. Figure 1 As shown, the electrode sheet is clearly cracked.
[0060] Example 7 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Same as Example 1.
[0061] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse them evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.08 kg of the above dispersant (accounting for 0.04% of the graphite mass) and 11.50 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0062] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 4956 mPa·s, the fineness to be 15 μm, and the solid content to be 56.5%. After standing for 72 hours, the viscosity was 5520 mPa·s, and the solid content to be 56.3%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0063] Example 8 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Same as Example 1.
[0064] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse them evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.1 kg of the above dispersant (accounting for 0.05% of the graphite mass) and 11.49 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0065] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 4302 mPa·s, the fineness to be 14 μm, and the solid content to be 56.6%. After standing for 72 hours, the viscosity was 5321 mPa·s, and the solid content to be 56.5%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0066] Example 9 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 10 g of sodium gluconate, 10 g of sodium tartrate, 10 g of polyethylene glycol monomethyl ether, and 70 g of deionized water. Add sodium gluconate, sodium tartrate, and polyethylene glycol monomethyl ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0067] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse them evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.06 kg of the above dispersant (accounting for 0.03% of the graphite mass) and 11.51 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0068] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 5005 mPa·s, the fineness to be 15 μm, and the solid content to be 56.7%. After standing for 72 hours, the viscosity was 6609 mPa·s, and the solid content to be 56.6%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0069] Example 10 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Same as Example 1.
[0070] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.02 kg of the above dispersant (accounting for 0.01% of the graphite mass) and 11.53 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0071] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 8258 mPa·s, the fineness to be 17 μm, and the solid content to be 56.3%. After standing for 72 hours, the viscosity was 11465 mPa·s, and the solid content to be 55.9%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0072] Example 11 This embodiment provides a dispersant for graphite anodes in lithium-ion batteries and an anode slurry prepared using the dispersant. The preparation method is as follows: (1) Preparation of dispersant Weigh out 20 g of sodium gluconate, 5 g of polyethylene glycol monomethyl ether, 5 g of alkylphenol polyoxyethylene ether, and 70 g of deionized water. Add sodium gluconate, polyethylene glycol monomethyl ether, and alkylphenol polyoxyethylene ether to the deionized water and stir at room temperature for 30 minutes until completely dissolved to obtain a dispersant.
[0073] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse them evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.06 kg of the above dispersant (accounting for 0.03% of the graphite mass) and 11.51 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0074] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 5229 mPa·s, the fineness to be 15 μm, and the solid content to be 56.5%. After standing for 72 hours, the viscosity was 7250 mPa·s, and the solid content to be 56.6%. Figure 1 As shown, the electrode sheet showed no obvious cracking.
[0075] Comparative Example 1 This comparative example provides a negative electrode slurry, and the preparation method is as follows: 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse evenly. 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 44.84 kg of deionized water was added to adjust the viscosity, resulting in a negative electrode slurry with a solid content of 43%.
[0076] Using the same performance testing method as in Example 1, the initial viscosity of the slurry was measured to be 5769 mPa·s, the fineness to be 19 μm, and the solid content to be 43.0%. After standing for 72 hours, the viscosity was 7677 mPa·s, and the solid content to be 42.3%. Figure 1 As shown, the electrode sheet is clearly cracked.
[0077] Comparative Example 2 This comparative example provides a dispersant and a negative electrode slurry prepared using the same. The preparation method is as follows: (1) Preparation of dispersant Weigh 20g of sodium gluconate and 80g of deionized water. Add the sodium gluconate to the deionized water and stir for 30 minutes at room temperature until completely dissolved to obtain a dispersant.
[0078] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse evenly. 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.09 kg of the above dispersant (accounting for 0.03% of the graphite mass) and 11.48 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0079] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 5512 mPa·s, the fineness to be 17 μm, and the solid content to be 56.3%. After standing for 72 hours, the viscosity was 8012 mPa·s, and the solid content to be 56.1%. Figure 1 As shown, the electrode sheet is clearly cracked.
[0080] Comparative Example 3 This comparative example provides a dispersant and a negative electrode slurry prepared using the same. The preparation method is as follows: (1) Preparation of dispersant Weigh 10 g of polyethylene glycol monomethyl ether and 90 g of deionized water. Add the polyethylene glycol monomethyl ether to the deionized water and stir for 30 minutes at room temperature until completely dissolved to obtain a dispersant.
[0081] (2) Preparation of negative electrode slurry 60 kg of artificial graphite and 0.6 kg of conductive carbon black SP were added to a double planetary mixing jar and stirred at a low speed of 20 rpm for 15 minutes to disperse evenly. Then, 30 kg of CMC adhesive with a solid content of 2% and 8 kg of PAA adhesive with a solid content of 6% were added and kneaded at a speed of 30 rpm for 30 minutes. Then, 0.18 kg of the above dispersant (accounting for 0.03% of the graphite mass) and 11.39 kg of deionized water were added and dispersed at a high speed of 2000 rpm for 60 minutes to obtain the negative electrode slurry.
[0082] (3) Performance testing The test method was the same as in Example 1. The initial viscosity of the slurry was measured to be 23055 mPa·s, the fineness to be 23 μm, and the solid content to be 56.2%. After standing for 72 hours, the viscosity was 26718 mPa·s, and the solid content to be 53.4%. Figure 1 As shown, the electrode sheet is clearly cracked.
[0083] The initial viscosity, viscosity after standing for 72 hours, and solid content data of Examples 1-11 and Comparative Examples 1-3 are as follows: Figure 2 As shown in the figure, the left side of the bar chart represents the initial viscosity, and the right side represents the viscosity after standing for 72 hours.
[0084] As can be seen from Examples 1-11 and Comparative Examples 1-3: Compared with Comparative Example 1, Examples 1 to 11 all achieved acceptable slurry viscosity for coating process under high solid content conditions of more than 56%, and the initial viscosity of Example 1 was comparable to or even lower than that of Comparative Example 1, proving that the dispersant of the present invention can increase the coatable solid content of the negative electrode slurry from 43% to more than 56% while maintaining the slurry at a low viscosity level.
[0085] Although Comparative Example 2 showed good performance in viscosity reduction, the electrode sheet cracked significantly, indicating that the viscosity-reducing and viscosity-stabilizing components did not have the function of releasing stress during the drying stage. The initial viscosity of the slurry in Comparative Example 3 was as high as 23055 mPa·s, which could not meet the coating requirements, and the electrode sheet also cracked significantly, indicating that the anti-cracking components did not have the ability to reduce viscosity and disperse.
[0086] Data from Examples 11, 1, 7, and 8 show that, within the range of 0.01% to 0.05%, the initial viscosity of the slurry decreases monotonically with the increase of dispersant dosage, and the increase in viscosity over 72 hours gradually decreases from 38.9% to 23.7%. This indicates that increasing the amount of dispersant is beneficial to improving the adsorption coverage and density of the adsorption layer on the particle surface, thereby enhancing the viscosity reduction and stabilization effects.
[0087] In summary, the dispersant for graphite anodes in lithium-ion batteries provided by this invention achieves high solids content and low viscosity in the slurry, excellent static stability, and effective crack prevention during electrode drying at extremely low dosages through the synergistic combination of viscosity-reducing and viscosity-stabilizing components and crack-preventing components. This solves the contradiction between high solids content and good processability in the prior art and has significant industrial application value.
[0088] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A dispersant for graphite anodes in lithium-ion batteries, characterized in that, The dispersant includes viscosity-reducing and viscosity-stabilizing components as well as crack-preventing components; The viscosity-reducing and viscosity-stabilizing components include one or more of sodium gluconate, sodium tartrate, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate. The anti-cracking component is one or more of polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, and polyvinylpyrrolidone.
2. The dispersant according to claim 1, characterized in that, The viscosity-reducing and stabilizing component has a mass percentage content of 10% to 20% in the dispersant; the crack-preventing component has a mass percentage content of 5% to 20% in the dispersant.
3. The dispersant according to claim 1, characterized in that, The dispersant also includes a solvent; The solvent is a polar solvent; Furthermore, the solvent is one or more of water, ethanol, and acetone.
4. The dispersant according to claim 1, characterized in that, The viscosity-reducing and stabilizing components are sodium gluconate, sodium tartrate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, or a combination of sodium gluconate and sodium tartrate.
5. The dispersant according to claim 1, characterized in that, The anti-cracking component is polyethylene glycol monomethyl ether, alkylphenol polyoxyethylene ether, polyvinylpyrrolidone, or a combination of polyethylene glycol monomethyl ether and alkylphenol polyoxyethylene ether.
6. The dispersant according to any one of claims 1 or 5, characterized in that, The molecular weight of the polyethylene glycol monomethyl ether is 200 to 2000.
7. The method for preparing the dispersant for the graphite anode of a lithium-ion battery as described in claim 1, characterized in that, Includes the following steps: The viscosity-reducing and stabilizing components and the crack-preventing components are dispersed in a solvent to obtain the dispersant.
8. A negative electrode slurry, characterized in that, It includes graphite, conductive agent, thickener, binder, solvent and dispersant as described in claim 1.
9. The negative electrode slurry according to claim 8, characterized in that, The solid content of the negative electrode slurry is 40% to 60%; the amount of dispersant added is 0.01% to 0.05% of the graphite mass.
10. A battery, characterized in that, Includes the negative electrode slurry as described in claim 8.
Citation Information
Patent Citations
Negative electrode slurry of lithium ion battery, preparation method of negative electrode plate and negative electrode plate
CN116190651A